Approach to the legal-criminal right of public health in Colombia (2021)
Recently, the discussion on the concept and specific scope of the legal-criminal good protected by Title XIII of the Colombian Penal Code has gained renewed interest. This article analyzes the issue in the international order, the evolution of national legislation in this regard is reviewed, the main positions adopted by jurisprudence and doctrine are exposed and, finally, a position is adopted on the matter.